The international mobility of Taiwanese students in Southeast Asia: The case of a university in Taiwan - Wang, Yi-Ju (Journal of Management and Business Education, 2022)
The international mobility of university students is one of the bases to enhance international competitiveness. This study aims to further understand the trends in Taiwanese international education. The case study was conducted at Providence University (PU), which have practiced internationalized education for years. This study adopts qualitative methodologies: documentary analysis and semi-structured interviews. The article analyzes the perceptions of PU students about their experiences as participants in an international mobility process in Thailand. We conduct questionnaires and in-depth interviews with them, in order to understand the satisfaction of students in terms of motivation, funding resources, cultural communication, team cooperation, and cross-border learning. This study shows joining cross-border learning does greatly improve on international mobility, especially in the acceptance in another culture and global exploration. Through communication between different cultures, the students have an improved understanding of Thai people’s communication behaviour.